Dampak Pandemi Covid terhadap Penguasaan E-skills Pegawai didalam Organisasi Publik - Qotrunada, Arifah Sitta (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2023)
The demand for expertise in managing information technology during apandemic has increased so sharply. This is because the development of digitalizationduring the pandemic has targeted all sectors including government institutions.Inevitably, the government sector and public organizations must adapt to this condition. In the public service sector, e-skills are one of the elements needed by almost all public employees. One of its functions is to manage and develop social media owned by public organizations so that they can become a means of communicating with the public. Especially during a pandemic, this has become one of the main choices for public organizations to be able to maintain maximum performance. Social media managed by public organizations must have content thatcan describe the functions and performance of government agencies. So the success ofpublic organizations in managing social media is strongly influenced by the skills ofemployees who create content on social media. One of the elements needed by publicemployees in the era of the Covid-19 pandemic is e-skills.